Some aspects of the legal nature of the Internet network - Харитонова, Олена Іванівна; Харитонова, Елена Ивановна; Kharytonova, Olena I.; Позова, Діна Дмитрівна; Позова, Дина Дмитриевна; Pozova, Dina D. (My University, 2016)
The article is devoted to the research on the Internet as a legal category. The legal nature of the Internet is determined as an object of legal impact. The main characteristics of the Internet, which are important for the understanding of this phenomenon, are listed. It is suggested author’s own definition of this category as a global publicly available information and telecommunications network with a complex multi infrastructure, which operates on the basis of crossborder management and gives opportunities for creating, posting information and access to it and also for providing related information services.

Стаття присвячена дослідженню мережі Інтернет як правової категорії. Визначено правову природу мережі Інтернет саме як об’єкту правового впливу. Наведено основні характеристики мережі Інтернет, які мають значення для розуміння сутності цього явища. Запропоновано авторське визначення цієї категорії як глобальної загальнодоступної інформаційнотелекомунікаційної мережі зі складною багаторівневою інфраструктурою, яка функціонує на засадах транскордонного управління та надає можливості для створення, розміщення інформації і доступу до неї, а також надання пов’язаних із цим інформаційних послуг.

Статья посвящена исследованию сети Интернет как правовой категории. Определена правовая природа сети Интернет именно как объекта правового воздействия. Приведены основные характеристики сети Интернет, которые имеют значение для понимания сущности этого явления. Предложено авторское определение этой категории как глобальной общедоступной информационно-телекоммуникационной сети со сложной многоуровневой инфраструктурой, которая функционирует на основе трансграничного управления и предоставляет возможности для создания, размещения информации и доступа к ней, а также предоставления связанных с этим информационных услуг.
Kharytonova O. I. Some aspects of the legal nature of the Internet network / O. I. Kharytonova, D. D. Pozova // Часопис цивілістики. – 2016. – Вип. 20. – С. 188-192.
Keywords: Internet network; Information and Telecommunications Network; legal nature; the object of the legal impact; мережа Інтернет; інформаційно-телекомунікаційна мережа; правова природа; об’єкт правового впливу; сеть Интернет; информационно-телекоммуникационная сеть; правовая природа; объект правового воздействия